(untitled) (Molecular Medicine Communications, 2022)
Statins induce hepatotoxicity via reduced levels of Coenzyme Q10, inflammation, and oxidative stress. Coenzyme Q10 is anti-apoptotic and possesses an antioxidative potential and hence has been studied for its hepatoprotective potential. However, owing to the differing mechanisms of prevention of damage and its reversal, we hypothesize that coenzyme Q10 will have varying efficacy as a protective versus a therapeutic approach. An experimental study of 3 weeks was conducted in the department of Pharmacology on a sample of 35 mice, randomly divided into 7 groups. Group 1 was used as a control. Group 2 received simvastatin 50mg/kg/day of simvastatin intraperitoneally (I/P). Group 3 received I/P 50mg/kg/day rosuvastatin. Group 4 received 50mg/kg/day of simvastatin+10mg/kg of coenzyme Q10. Group 5 received 50mg/kg/day of rosuvastatin+10mg/kg of coenzyme Q10 I/P. In group 6 simvastatin 50mg/kg & 7 rosuvastatin 50mg/kg was given for a week, and 10mg/kg of Coenzyme Q10 was started in the 2nd week and continued for 2 weeks. Hepatic damage was observed in groups 2,3,6 and 7 indicated by raised ALT levels of 320.4, 179.8, 301.4, and 186.8 and raised AST levels of 320, 196, 421.4, and 307.6. Bilirubin stayed within normal limits. Coenzyme Q10 prevents statin-induced liver damage but has no role as a therapeutic agent once the liver damage has already occurred.